Aminas bioativas em carne de peito de frango e em ovos de consumo produzidos no Estado de Minas Gerais - Debora Cristina Sampaio de Assis (2014)
In order to evaluate the levels of bioactive amines in poultry products produced in Minas Gerais were collected, by state inspection service and federal, 56 samples of commercial eggs and 160 samples of broiler chicken breast from the five regions of the state. The amines: phenylethylamine (only in commercial eggs), putrescine, cadaverine, histamine, tyramine, spermidine and spermine were determined. The analytical method, by high performance liquid chromatography (HPLC), was validated and the results showed high selectivity and separation of all amines, linearity (correlation coefficient more than 0,99), high recovery index, low limits of detection and limits of quantification between 0,09 and 0,1mg/100g. The results of the analyzes of chicken breast samples showed the presence of amines spermidine and spermine in all samples, at concentrations between 1,868-6,219mg/100g and 4,915-6,496mg/100g, respectively. The amines putrescine, cadaverine, histamine and tyramine were also found, but in low concentrations in the chicken breast. In the samples of commercial eggs, were detected in low concentrations the amines putrescine, cadaverine, phenylethylamine, histamine, tyramine and spermidine. Putrescine was detected in all samples and cadaverine was the second most prevalent amine in the eggs. It was concluded that amine levels found, both in the chicken breasts and in eggs, were low and do not represent risks to consumer health and that the chicken meat is na important source of polyamines, especially spermidine and spermine.